Rethinking Daycare in Amhara Region of Ethiopia: Bridging the Gap between Needs and Practices - Tessema, Mesret Getachew; Yizengaw , Simegn Sendek; Kassa , Ebabush Yerdaw; Mengtie, Misaye Mulatie; Fufa, Yeabkal Tilahun; Asnakew, Hayimanot Ezezew (Ethiopian Renaissance Journal of Social Sciences and the Humanities, 2025)
The main aim of this research was to explore daycare practices, beliefs and challenges in two Amhara metropolitan cities. The study informed with qualitative approach in which data were gathered using interview and observation from caregivers, parents, daycare owners and government officials. Analysis revealed a common misconception: daycares were often referred to as “yehitsanat makoya” (children’s stay centers), despite variations in the understanding of the name. Additionally, the primary purpose of daycare centers (services for age six months to three years children), according to most participants, was to free up mothers’ time for work. It was found out that the primary focus of caregivers is on children’s personal care routines; age-appropriate daily schedules were not integrated and repetitive activities dominated. Parents’ responsibilities were limited to fulfilling material requirements such as providing food, clothing supplies and monthly fees. Respondents emphasized infrastructure as a key daycare element. Besides, lack of awareness, limited capacity building, and insufficient supervision and support from concerned bodies are major challenges for delivering quality daycare services. Based on the findings, it is recommended that relevant authorities should make close consultation with the daycare centers and create platforms to improve daycare service delivery in the cities.